Alienation Through Language: A Socio-Linguistic Study of Identity and Marginalisation in Dazai Osamu’s No Longer Human - Fauzi, S.S, M.Pd, Rizki; Pribadi, Kayla Zahra Prawoto; Mappaita, Suci Pole (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
The article explores the interface of linguistic action and social process from an applied linguistic perspective, taking Dazai Osamu's novel No Longer Human as a case study. This study discusses the extent to which linguistic representations mirror the psychological alienation, social exclusion, and disjunctive self-identity of the main protagonist. By using discourse analysis in conjunction with sociolinguistic theories, the article investigates language's function of constructing, reproducing, and unveiling the social alienation of individuals who are outsiders to social norms in post-war Japan.